The UMKM Terhubung Platform Teknologi Digitalisasi Dapat Bertahan Terhadap Dampak Pandemic Covid-19 di Kecamatan Kramat Jati, Jakarta Timur - Edward Baringin Oloan Sihite (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
PKM activities have been carried out on UMKM connected to digitalization technology platforms that can withstand the impact of the COVID-19 pandemic in the Kramat Jati sub-district, East Jakarta. The purpose of this PKM is to narrate that UMKM that are growing connected to the digitalization platform. The idea of this incident raised UMKM using a digitalization technology platform as a solution in the midst of the COVID-19 pandemic in the Kramat Jati sub-district, East Jakarta. The PKM implementation method is carried out in the Keramat Jati sub-district where UMKM actors trade. The selected UMKM participants are fostered for business digitization, such as the development of digitalization technology applications and digitalization transaction payments. The instruments used are website applications, digitalization payments, and social media applications. As a result, efforts were made to increase UMKM customer traffic through online promotions on social media (FB and IG) or through Google and e-commerce marketing platforms. Promotional efforts have been made to attract potential customers and introduce the UMKM business to the wider community online.The conclusion proves that UMKM that grow are connected to the digitalization platform, it turns out that not all micro, small and medium enterprises (UMKM) are affected by the COVID-19 pandemic. UMKM that do business by utilizing the digitalization technology platform have actually grown significantly.